Axial jerks: a clinical spectrum ranging from propriospinal to psychogenic myoclonus - van der Salm, Sandra M. A. (Springer-Verlag, 2010)
Propriospinal myoclonus (PSM) is a rare disorder with repetitive flexor, arrhythmic jerks of the trunk, hips and knees. Its generation is presumed to relay in the spinal cord. We report a case series of 35 consecutive patients with jerks of the trunk referred as possible PSM to a tertiary referral center for movement disorders. We review classical PSM features as well as psychogenic and tic characteristics. In our case series, secondary PSM was diagnosed in one patient only. 34 patients showed features suggestive of a psychogenic origin of axial jerks. Diagnosis of psychogenic axial jerks was based on clinical clues without additional investigations (n = 8), inconsistent findings at polymyography (n = 15), regular eye blinking preceding jerks (n = 2), or the presence of a Bereitschaftspotential (BP) (n = 9). In addition, several tic characteristics were noted. Almost all patients referred with possible PSM in our tertiary referral clinic had characteristics suggesting a psychogenic origin even in the presence of a classic polymyography pattern or in the absence of a BP. Clinical overlap with adult-onset tics seems to exist. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00415-010-5531-6) contains supplementary material, which is available to authorized users.